The Implementation of Communicative Language Teaching in English Practice - Arini Sabrina (Universitas Ahmad Dahlan, 2020)
2013 Curriculum now has been implemented so widely in Indonesia, especially in English teaching and learning process. It delineates some focal points like student-centered active learning and contextual teaching which hopefully brings the students to learn more effectively. Furthermore, there is an apparent unanimity that the curriculum may lead the meaningfulness of learning. In relation to English teaching approach, Communicative Language Teaching (CLT) is likened to the latest curriculum. CLT emphasizes on the context and authenticity. Thus, this approach should go along with 2013 Curriculum. This study aims at finding out the implementation of CLT in line with the curriculum, since many previous studies alert some problems happening while CLT is applied not in ESL as its birthplace, yet in EFL context. In fact, Indonesia perceives English as foreign language. But, there are still few studies related to this approach. After observation and document tracking are conducted, it is concluded that Scientific Approach and Communicative Language Teaching Approach are able to blend to create more effective communicative learning.